A Multilevel Quasi Matrix Converter Design for SRM Drives In EV Applications - Syeda Fatima Ghousia (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
This paper presents a novel idea of developing an absolute, general choice multilevel asymmetric power converter for switched reluctance motor (SRM) drive suitable specifically in electric vehicle applications. For SRM drives, the suitability of a particular inverter circuit changes with the motor geometry. It is in contrast to the drives operating with sinusoidal voltages and currents where the inverter topology is independent of the motor design. Specifically, in the case of SRM, the number of the stator/rotor poles and the related issues of the dwell angle and current overlap parameters affect the inverter choice. The multilevel power converters open up a great deal of possibilities in control and can be used to achieve flexible current profiling but with the added benefit of lower switching frequencies and hence less converter losses. The idea is to use a matrix converter topology for finer control on flexible current profiling with three terminals of dc voltage source at the input. To illustrate the potential benefits of this converter, with SRM for EV applications, a Simulink model of proposed multilevel matrix converter was tested in interface with finite element model of the SRM.DOI: http://dx.doi.org/10.11591/ijpeds.v2i2.224